Wegener's granulomatosis and differential diagnosis of mucosal leishmaniasis - Rojas Jaimes, Jesús (2021)
ABSTRACT Granulomatosis with polyangiitis with nasal septal perforation can be confused with infectious diseases such as mucosal leishmaniasis, so these cases warrant an in-depth study in order to provide the correct treatment. Among the main characteristics to consider to define a Wegener's granulomatosis as opposed to an infectious disease are vasculitis, lymphadenopathy, and sinusopathy.